What is "Islamic" art?: between religion and perception - Shaw, Wendy M. K., 1970- (Cambridge, United Kingdom : Cambridge University Press, 2019)
This book began as an exploration of the image in Islam. It ended up exploring how one might relinquish concepts like the image and art to conceive of perception through an Islam, often overshadowed by politics, essential to a sense of emotive knowledge that emerges through engagement with the arts. Instead of defining the image, art, or religion, this book asks: What is art if the primary sensory organ is neither eyes nor ears, but the heart? Where are the boundaries between the senses as we take in the world? What is art if dreams and visions are as real as materiality? How can art make-present, and not just re-present?
Introduction : from Islamic art to perceptual culture -- The Islamic image -- Seeing with the ear -- The insufficient image -- Seeing with the heart -- Seeing through the mirror -- Deceiving deception -- The transcendent image -- The transgressive image -- Mimetic geometries -- Perspectives on perspective -- Conclusion : out of perspective.
Includes bibliographical references [pages 336-359] and index.
Keywords: Islamic art